IMPELEMENTASI PENJAMINAN MUTU PENDIDIKAN ISLAM MELALUI MADRASAH DI INDONESIA - Syahlarriyadi (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2023)
The beginning of March 2020 was marked by the entry of Covid-19 into Indonesia which later became a Covid-19 pandemic marking various astonishing changes. Changes in various aspects of life such as social, religious, political, defense, and security science and technology are increasingly felt. This fact confronts a dilemmatic educational problem, where the quality of education which is the standard of national education quality is faced with an atmosphere of modernization and globalization, which is required to be able to play an active and dynamic role and be able to bring and contribute to the improvement of human morals, both at the theoretical and practical intellectual level. The problem of education in Indonesia tends to be oriented to the fulfillment of physical development needs through the preparation of human resources who have professional competence or are able to work professionally, it is time for Islamic education to reformulate holistic and integrative Islamic education with the vision of advancing Islamic civilization to be very important.